3b-6-12b-7=

Simple and best practice solution for 3b-6-12b-7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3b-6-12b-7= equation:


Simplifying
3b + -6 + -12b + -7 = 0

Reorder the terms:
-6 + -7 + 3b + -12b = 0

Combine like terms: -6 + -7 = -13
-13 + 3b + -12b = 0

Combine like terms: 3b + -12b = -9b
-13 + -9b = 0

Solving
-13 + -9b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + -9b = 0 + 13

Combine like terms: -13 + 13 = 0
0 + -9b = 0 + 13
-9b = 0 + 13

Combine like terms: 0 + 13 = 13
-9b = 13

Divide each side by '-9'.
b = -1.444444444

Simplifying
b = -1.444444444

See similar equations:

| -8(2t+9)=-168 | | 4(f-5)=-4 | | (x+4)(3-5x)=6-3(x-1) | | (5x-10)=6x+5 | | -(3x-7y+1)= | | x=1287.4(17)+48470 | | 2(x-10)+(x-10)=46 | | 2(6x+2)=0 | | x^2+84-520=0 | | (3x-1)(2x+1)=0 | | x=1287.4(2017)+48470 | | 10(s-4)=-146 | | =31x-18y | | (2x^2-3x^3)-(9x^2-5x^3)=0 | | 100000=1287.4x+48470 | | (2x^2-3x^3)(9x^2-5x^3)=0 | | 22-3x=2 | | 18-2(5-3x)=-5x-3 | | (2x^2-3x^3)(9x^2-5x^3)= | | 4(d-8)+3= | | (4x-13y)-(-27x+5y)= | | 3(x+4)+3=-5(x-8)-1 | | 6(t+4)=-6 | | 7(r+9)= | | 10-48x-12=27x+36x | | 6w-w+5w= | | (16-10)x-35000=0 | | 5x(3-13)=100 | | 7(3s+10)=238 | | 10x+8=4x+3 | | 2(2l+2)=24 | | 8x-32=5+10x |

Equations solver categories